2021
DOI: 10.1038/s41598-021-83978-4
|View full text |Cite
|
Sign up to set email alerts
|

Forager and farmer evolutionary adaptations to malaria evidenced by 7000 years of thalassemia in Southeast Asia

Abstract: Thalassemias are inherited blood disorders that are found in high prevalences in the Mediterranean, Southeast Asia and the Pacific. These diseases provide varying levels of resistance to malaria and are proposed to have emerged as an adaptive response to malaria in these regions. The transition to agriculture in the Holocene has been suggested to have influenced the selection for thalassemia in the Mediterranean as land clearance for farming encouraged interaction between Anopheles mosquitos, the vectors for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 76 publications
1
42
0
Order By: Relevance
“…Although non-specific, this pathological feature is consistent with hematopoiesis observed in some cases of thalassemia intermedia (Adamopoulos & Petrocheilou, 2019;Cambouris, 1989) rather than cortical rarefaction observed in thalassemia major, such as in the case reported here. Extramedullary hematopoiesis of long bones was also observed in the pre-agricultural sample from Con Co Ngua reported by Vlok et al (2021). Paleohistological cross sections from these long bones displayed significant evidence of endosteal macroporosity consistent with clinical descriptions of bone loss in modern thalassemic patients.…”
Section: Paleopathological Implications Of Thalassemia Diagnosis In Prehistorysupporting
confidence: 74%
See 3 more Smart Citations
“…Although non-specific, this pathological feature is consistent with hematopoiesis observed in some cases of thalassemia intermedia (Adamopoulos & Petrocheilou, 2019;Cambouris, 1989) rather than cortical rarefaction observed in thalassemia major, such as in the case reported here. Extramedullary hematopoiesis of long bones was also observed in the pre-agricultural sample from Con Co Ngua reported by Vlok et al (2021). Paleohistological cross sections from these long bones displayed significant evidence of endosteal macroporosity consistent with clinical descriptions of bone loss in modern thalassemic patients.…”
Section: Paleopathological Implications Of Thalassemia Diagnosis In Prehistorysupporting
confidence: 74%
“…Recent research that combined macroscopic and paleohistological approaches identified thalassemia in a further two prehistoric sites from Northern Vietnam (Vlok et al, 2021). One site (Man Bac) is contemporaneous with the cases reported by Tayles (1996), where up to Weatherall, 2008;Figure 13).…”
Section: Paleopathological Implications Of Thalassemia Diagnosis In Prehistorymentioning
confidence: 99%
See 2 more Smart Citations
“…Other recent genetic studies have demonstrated the prominence of malaria-related blood pathologies (thalassemia) in prefarming populations in southeast Asia as well (Vlok et al, 2021).…”
Section: Sickle Cell Anemiamentioning
confidence: 99%